1976
DOI: 10.1001/archpedi.1976.02120100041006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia After Renal Transplantation in Children

Abstract: \s=b\ A cross-sectional survey of 32 children who received renal allografts was undertaken to evaluate lipid profiles in a pediatric transplant population. Ages ranged from 8 to 18 years, and serum creatinine concentrations varied from 0.5 to 5.6 mg/100 ml (mean, 1.4 mg/100 ml). Fifty percent of patients showed an abnormal lipoprotein electrophoresis, and these were evenly divided between type II and type IV patterns. The data suggest that patients with type II pattern tend to be receiving higher doses of pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…After kidney Tx, hyperlipidemia has been reported in up to 66% of children who did not receive CsA, suggesting a role for prednisone [11,16,17,18,19]. Saldanha et al [16] showed that TG (but not TC) was lower in Tx recipients on alternate-day (versus daily) prednisone. Saldanha et al [16] showed that TG (but not TC) was lower in Tx recipients on alternate-day (versus daily) prednisone.…”
Section: Discussionmentioning
confidence: 99%
“…After kidney Tx, hyperlipidemia has been reported in up to 66% of children who did not receive CsA, suggesting a role for prednisone [11,16,17,18,19]. Saldanha et al [16] showed that TG (but not TC) was lower in Tx recipients on alternate-day (versus daily) prednisone. Saldanha et al [16] showed that TG (but not TC) was lower in Tx recipients on alternate-day (versus daily) prednisone.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in adult renal transplant recipients is clearly a risk factor for hyperlipidemia [5,15,20]. We chose to use BMI, since our patients were all of pediatric age when body weight can only be properly assessed in conjunction with height.…”
Section: Discussionmentioning
confidence: 99%
“…However a few studies have investigated the incidence of post-renal transplant hyperlipidemia in pediatric patients. Some have shown that in children risk factors for hyperlipidemia include the use of prednisone and cyclosporine [13,15]. However, Sharma et al [16] demonstrated that cyclosporine was not a risk factor for hyperlipidemia in 33 pediatric patients several years after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with results obtained in two studies [3,5] of children with kidney graft was difficult, since these investigations did not refer to homogenous age groups similar to ours, and since the different types of hyperlip idemia were not considered separately.…”
Section: Discussionmentioning
confidence: 67%